Genotype-phenotype correlation of WT1 mutation-related nephropathy in Chinese children - Chen, Huanru; Zhang, Miao; Lin, Jinai; Lu, Jieyi; Zhong, Fazhan; Zhong, Fu; Gao, Xia; Liao, Xin (Frontiers in Pediatrics, 2023)
This study aimed to analyze the clinical characteristics of nephropathy associated with WT1 gene mutations in Chinese children and explore the relationship between genotype and clinical phenotype. Methods: Cases diagnosed at the Guangzhou Women and Children's Medical Center, were combined with those retrieved from PubMed and China National Knowledge Infrastructure(CNKI) databases from January 2015 to June 2022 and integrated into a study cohort. The relationship between genotype and age of onset, clinical phenotype, and pathological type were retrospectively analyzed. The center enrolled 15 confirmed children: seven cases of non-simple nephropathy, including Denys-Drash syndrome (DDS) and Frasier syndrome (FS); eight cases of isolated steroid-resistant nephrotic syndrome (ISRNS); and 13 cases (86.7%) that progressed to end-stage renal disease(ESRD). The initial hemoglobin and bicarbonate levels of patients with clinical non-simple nephropathy were significantly lower than those with simple nephropathy, whereas the serum creatinine levels were higher than those of patients with simple nephropathy. A total of 75 cases of nephropathy associated with WT1 mutations in the study cohort met the inclusion and exclusion criteria. The most common clinical manifestations of WT1 mutations in this cohort were DDS (29/75, 38.7%) and ISRNS (37/75, 49.3%). A renal biopsy was performed in 43 patients, and the common types of renal pathology were focal segmental glomerulosclerosis (23/43,53.5%) and DMS (13/43,30.2%). Within the cohort, there were 12 cases (16.0%) in the exon 8 mutation group, 32 (42.6%) in the exon 9 group, 19 (25.3%) in the intron 9 group, and 12 (16.0%) in other gene site mutation groups. Common sites of WT1 mutations in Chinese children were exons 9 and intron 9. Exon 8 mutations were uniquely correlated with the age of onset within three months (5/7; 71.4%; Adjusted standardized residual (AR) = 4.2) and the pathological type of DMS. The renal survival time in the exon 8 mutation group was the shortest (P = 0.003). The molecular and biological characteristics of WT1 mutation-related nephropathy determine the clinical type, pathological features, and renal survival time of the disease; and there was a strong correlation between the genotype and clinical phenotype.